As representações da mídia televisiva sobre as mortes violentas na Tríplice Fronteira: um estudo comparativo entre Brasil e Paraguai - Silva, Maria Tereza Pereira da (2018)
This thesis aims to analyze how violent deaths are portrayed in television press in the Triple Frontier region, more specifically between Brazil and Paraguay, through the television programs “Tribuna da Massa” from Foz do Iguaçu/Brazil and “24 horas” from Ciudad Del Este/Paraguay. This qualitative research uses as data source television programs from each side of the border. Ten stories related to violent deaths from each side of the border and from each news program were selected. The temporal cut for the Brazilian television program was between the months of May to July of 2017, and between January to August of 2017 for the Paraguayan program. A longer period was necessary to the Paraguayan program due to the rate of violent deaths to be lower in Paraguay than it is in Brazil. The comparative method was adopted due to its presence in Sociology studies since the classics of the subject, and because this method is able to display the similarities, differences, models, constancies amongst other aspects of the object analyzed. The relevance of the space delimitation is the context of an international border with significant relevance to the respective countries, besides being a place known for violent practices and for crimes like drug trafficking, smuggling and embezzlement aside from a high tax of lethality. Through the comparison on how the violent deaths are portrayed in the two TV News it is possible to realize the standards of manipulation and addressing. Despite the television programs have different coverage and different hosting styles, they share addressing formats and common global standards. The approach on communicating the deaths are different when it comes to displaying the images of the bodies, but the way stories and speech are composed have similar aspects.